University Engineering Faculty Depend on Scholarly Journals, Web Resources, and Face-to-Face Consultations to Help Them with Research - Newton Miller, Laura (Evidence Based Library and Information Practice, 2012)
Objective – To study the information-seeking behaviour of engineering faculty. Design – Online survey; Purposive sample. Setting – Engineering departments of 20 large public universities in various regions of the United States. Subjects – 903 engineering faculty members (including 35% professors; 24% associate professors, 23% assistant professors, and 17% ranked as adjunct faculty, instructors, lecturers, professors emeriti and “other”). Methods – 4905 researchers were sent an email invitation to complete a 12-item survey with open and closed questions. Email addresses were gathered from university websites. Main Results – 96% of those surveyed find access to online scholarly journals (current and backfiles) as very important or important. 71% believe access to the physical book collection is very important or important. 56% feel that access to electronic book collections is very important or important. (Further analysis revealed a difference between newer and older faculty- 62% of newer faculty and 52% of faculty in field for 16 or more years think electronic book collections are important). Print subscriptions to journals are important to only 37% of respondents, and providing space to conduct research is important to only 36% of those surveyed. Besides attending conferences and scanning journals, face-to-face discussion with students and colleagues was a key resource for faculty for keeping current in the engineering field. 81% seek information at least weekly to prepare for lectures, about 74% at least monthly to conduct research or write publications, and 77% at least monthly to remain current in their field. 73% visited the physical library fewer than five times in the past year, but researchers were surprised that almost half (47%) rated assistance from library staff as important or very important. 70% see interlibrary loan services as important or very important. Conclusion – Engineering faculty rely on scholarly journals, Internet, and other electronic resources for their research. They depend on face-to-face consultations with students and colleagues. The physical space of the library is less important.